Tinjauan Penyebab Pengembalian Klaim BPJS Kesehatan Pasien Rawat Inap - Nina Dwi Astuti; Andrika Nurul Hidayah (Jurnal Rekam Medis dan Informasi Kesehatan, 2022)
Claim returns for Social Security for Health Agency (BPJS Kesehatan) always become a cliché in the field of health budgeting in the National Health Security (JKN) era. Some studies have examined factors causing claim return; however, the issue has not been figured out yet because every hospital has different troubles. This study was conducted to identify the troubles possibly causing claim returns faced by hospitals. This qualitative study was conducted at a type-C hospital owned by the government in Central Java province. In-depth interviews were conducted with assembling staff, coder, case-mix officer, internal verificatory, and head of the medical record unit. Results showed that claim returns occurred because the hospital information system had not been integrated with e-claim and v-claim apps. The hospital lacked the number of case-mix officers, and old-fashioned information about the INA CBGs payment scheme from the officers including coders, doctors, and other medical officers; the hospital also had inadequate supporting facilities such as echocardiography and endoscopy, and its staff had a lack of work experience and training for coders. Managerial support is tremendously required to solve the issues related to claim returns for BPJS Kesehatan.